Ichnotaxonomy of bird-like footprints: an example from the Late Triassic-Early Jurassic of northwest Argentina - de Valais, Silvina; Melchor, Ricardo Nestor
The ichnotaxobases previously used to classify avian-like footprints, at the ichnogeneric, ichnospecific, and ichnofamily level, are varied and contrasting. Consequently, an agreement on the most adequate taxobases to use for classifying these vertebrate trace fossils is necessary. The authors follow an ichnotaxonomy treatment independent to the age, locality provenance, and possible tracemaker of the trace fossils. The ichnotaxobases used to classify tracks with avian affinities at ichnogeneric and ichnospecific levels are evaluated and a proposal is made for useful and appropriate ichnotaxonomic criteria, considering those currently in use. Previous criteria used to distinguish avian footprints from non-avian theropod or ornithischian tracks are discussed. These concepts are applied to the avian footprints from the upper part of the Late Triassic-Early Jurassic Santo Domingo Formation from La Rioja province, northwest Argentina, which has yielded a diverse assemblage of trace fossils. The most conspicuous avian footprint is Gruipeda dominguensis isp. nov. The ichnogenus Gruipeda Panin and Avram, 1962 is revised and an emendation of its diagnosis is suggested. Trisauropodiscus Ellenberger, 1972, from South Africa and Antarctichnus Covacevich and Lamperein, 1970 from Antarctica are considered as junior synonyms of Gruipeda. Three other morphotypes of avian footprints are left under open nomenclature: one is assigned as cf. Alaripeda isp., other as bird-like footprints type C, and the third bird-like footprint with elongated drag marks. These specimens could be related to avian origin, but the possibility of a case of convergence with birds is not discarded. The presence of tracks with a wide total divarication produced in ephemeral fluvial systems with shallow ponds and mudflats suggest that it is likely the attainment of a convergent avian-form feet to improve controlled movements. Fil: de Valais, Silvina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Museo Paleontológico Egidio ...